Optical fiber based dosimeter sensor: Beyond TLD-100 limits - Mandiraji, G.A.; Ghomeishi, M.; Dermosesian, E.; Hashim, S.; Ung, N.M.; Adikan, Faisal Rafiq Mahamd; Bradley, D.A. (Elsevier, 2015)
This work investigates the suitability of single mode optical fibers (SMFs) as ionizing radiation dosimeter sensors. Thermoluminescence (TL) response studies have been carried out to investigate the performance of two commercial optical fibers, SMF-1 and SMF-2, with different Ge-doping concentrations of 4.9 and 4.3 wt, respectively, exposed to 0.5 to 8 Gy doses under 6, 9, and 20 MeV electron radiations. The performance parameters include dose response linearity and sensitivity, energy dependency, glow curve analysis, minimum detectable dose, repeatability, fading effects and optical absorption. The TL dose response of SMF-1, the fiber with the greater Ge concentration of the two, was found to be in excess of 6.3 and 3.2 times that of SMF-2 and TLD-100, respectively. SMF-1 demonstrated capability for detecting a minimum dose of as low as 6 mGy, being some 3.2 times superior to that of TLD-100. The results underline the potential of these optical fibers as next-generation alternative dosimeter sensors for detection of ionizing radiation. (C)2014 Elsevier B.V. All rights reserved.